Aging & community health: a university–community partnership project. Issue 4 (3rd April 2018) - Robinson-Dooley, Vanessa; Dumont, Kelly; Riapos, Jennifer A
ABSTRACT: The purpose of this paper is to discuss how university–community partnerships can be utilized to provide affordable and accessible health care for the elderly at community health clinics. A review of community health clinics, usage data from 2013 to 2014 by a sample of aging individuals will be described along with faculty perspectives about the usefulness of the university partnership and suggestions for improving future partnerships. Recommendations for future university–community partnerships are discussed.